Impact of Talent Retention Practices on Employee Performance: Examining the Link between Talent Retention and Employee Performance in the Service Sector (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The purpose of the study was to examine the effect of talent Retention practices on employee performance. The present study was descriptive and exploratory in nature as the study will describe the current talent attraction practices in service sector and also seeks to explore the effect of talent retention practices on employee performance. The sources of data collection will be primary and secondary. Primary data for the purpose of the study was collected through questionnaire by employees of different healthcare organizations. Secondary data is collected through the literature review and through scanning hospitals document. In this study the sampling frame was all private and public healthcare organizations in India. The target population for the purpose of the study was Delhi and NCR. For the purpose of the study data of 400 individuals is collected from different levels from 30 organizations. Respondents were employees of the organizations. Non-Probability Sampling Technique was used and specifically, Judgmental sampling technique was used. The study found that higher the talent retention practices better will be the employee performance.